Seasonal variation of fluxes of planktic foraminiferal tests collected by a time-series sediment trap in the central Bay of Bengal during three different years. (May 2022) - Maeda, Ayumi; Kuroyanagi, Azumi; Iguchi, Akira; Gaye, Birgit; Rixen, Tim; Nishi, Hiroshi; Kawahata, Hodaka
Abstract: Sediment trap samples from the southwestern Bay of Bengal were obtained at a water depth of about 900 m at sampling intervals of 17–27 days during three time periods (November 1988 to October 1989, December 1990 to October 1991, and January 1993 to October 1993). The planktic foraminifer abundances and assemblages of the samples were analyzed, and the factors governing the assemblages and their potential as indicators of climate and ocean processes in the sedimentary record were examined. We identified 28 species of planktic foraminifers in the samples, of which seven species accounted for more than 80% of each assemblage. The highest fluxes of planktic foraminifer tests were generally observed during the summer and winter monsoon seasons, and the lowest fluxes were observed during the intermonsoon seasons, especially from March to May. Periods of enhanced primary production during monsoons were accompanied by a sharp increase in the flux of Globigerina bulloides, whereas nutrient depletion in the surface ocean in spring led to subsurface small size plankton production and low planktic foraminifer test fluxes. The seasonality of foraminiferal assemblages and fluxes was controlled mainly by seasonal surface and subsurface primary production. The transition of abundant species from subsurface dwellers to surface ones throughout the monsoon season can be attributed to initial subsurface primary and secondary production being succeeded by enhanced surface production. The foraminiferal flux pattern differed among the three observation periods, especially in summer, because of interannual variation in the regional physical forces that induce nutrient replenishment at the surface. However, the consistent features of the flux pattern, with peaks during the monsoon seasons and minimal values in spring, suggest that our results reveal the essential, long-term flux pattern of planktic foraminifers in the southwestern Bay of Bengal. Highlights: Sediment trap samples in the Bay of Bengal revealed 28 planktic foraminifer species. The seven major species were divided based on their feeding and reproduction styles. The test flux peaked during the monsoon periods and was low in March–May. The test flux seasonality was affected by productivity and food-web structure.